2012
DOI: 10.1016/j.enpol.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic performance of heating systems for energy-efficient dwellings: Case of passive and low-energy single-family houses

Abstract: In order to reduce the energy consumption of the building stock, a major trend is to drastically reduce the space-heating (SH) needs by improving the thermal performance of the envelope. In general, this measure is combined with efficient heating systems to minimize the delivered energy and greenhouse gas emissions. Nevertheless, these better systems are often more expensive so that the extra-investment could be hardly recovered for small-scale energy consumption. The main objective of the article is to show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 5 publications
(8 reference statements)
1
26
0
1
Order By: Relevance
“…In terms of payback time, savings on these energy costs counterbalance more slowly the extra-investment that must often be accepted to afford a more energy-efficient heating system. Particularly for a passive house, it can be shown that selecting a heating system with a low investment cost is a necessary condition to reach cost effectiveness [1]. This low investment is possible using a wood stove.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of payback time, savings on these energy costs counterbalance more slowly the extra-investment that must often be accepted to afford a more energy-efficient heating system. Particularly for a passive house, it can be shown that selecting a heating system with a low investment cost is a necessary condition to reach cost effectiveness [1]. This low investment is possible using a wood stove.…”
Section: Introductionmentioning
confidence: 99%
“…The global costs method is used in Poland and in many European countries to establish the requirements of thermal protection of the buildings [21,[23][24][25][26][27][28][29][30][31][32][33]. The For the analysed buildings only in case of bio-mass boiler application the energetic optimum, assumed by global cost method, lies in the area of the used energy at the level of EU 15 .…”
Section: Cost's Optimal Resultsmentioning
confidence: 99%
“…The economic and environmental feasibility of the EPBD-recast comparative framework methodology has been validated, before [15][16][17][18][19] and after [1,[20][21][22][23] stipulating the directive.…”
Section: The Economic and Environmental Feasibility Of The Epbd-recasmentioning
confidence: 99%
“…According to a previous literature review conducted by the authors [1], it is concluded that few economic scenarios or design options are addressed in nZEB related studies. None of the studies of Kumbaroglua and Madlener [2], Hasan et al [3], Papadopoulos et al [4], Georges et al [5], Kurnitskia et al, [6], Marszal et al [7], Munjur et al [8]. and Attia [9] investigated comprehensively the impact of the economic assumptions on the cost-optimal energy performance level (CO-EPL) towards nZEBs, in line with the EBPD-recast 2010 [10].…”
Section: Introductionmentioning
confidence: 99%